Occurrence and Distribution of Major Seedborne Fungi Associated with Phaseolus Bean Seeds in Ethiopia - Mohammed Yesuf,; Somsiri Sangchote, (Agriculture and Natural Resources, 2005)
A total of 245 seed samples of Phaseolus bean; 172 common beans, 51 climbing beans and 22 green beans were collected from various bean growing areas during 2003 crop season. The incidence and severity of seed infection by the major fungal diseases of bean varied between localities, bean types and cropping practices. Thirteen seed-borne fungal pathogens of different genus were identified from seed samples collected from the major bean growing regions of Ethiopia. The incidence of different seedborne fungi ranging between 0.2 to 14.5% was found to vary from location to location and growing conditions. Among them, Colletotrichum lindemuthianum, Phaeoisariopsis griseola, and Ascochyta phaseolorum were the most widespread and damaging seedborne fungal pathogens associated with Phaseolus bean seeds in Ethiopia. From the total seed samples collected, 26.2%, 19.6% and 13.6% of common bean, climbing bean and green bean respectively were infected by C. lindemuthianum, whereas infection by P. griseola was 18.6% and 15.7% on common bean and climbing beans seeds respectively. Green bean seeds were not infected by the latter two fungi. Seeds collected from south, southwest, and western part of Ethiopia showed heavy seed infection by these major fungal pathogens, whereas seeds produced in dry areas with minimum rainfall or under irrigation showed very low seed infection. Phytophthora rot of beans caused by Phytophthora sp. was also detected from green bean pods and immature seeds produced under irrigation in the central rift valley of the country. The geographic distribution of major seed-borne fungi of Phaseolus beans was mapped.